DETERMINAN KUALITAS INFORMASI AKUNTANSI PADA PT. PERKEBUNAN NUSANTARA II - Mulatua P. Silalahi; Gracesiela Yosephine Simanjuntak; Rike Yolanda Panjaitan; Duma Rahel Situmorang (Universitas Methodist Indonesia, 2022)
The purpose of this study was to examine the effect of the use of information technology, user experience and intensity of use on the quality of accounting information at PT. Nusantara Plantation II. The basic population of this research is the financial, administrative and human resource management staff of PT. Nusantara Plantation II. This study uses a saturated sampling technique to obtain the sample, so that all employees are used as samples. The data analysis technique used is descriptive statistical analysis and multiple linear analysis. The results showed that simultaneously the variable use of information technology, user expertise and intensity of use and user expertise have a significant effect on the quality of accounting information, while the use of information technology and user expertise partially has a significant positive effect on the quality of accounting information, while the intensity of use has no significant effect on the quality of accounting information PT Perkebunan Nusantara II.